Leveraging Qardhul Hasan Practices from Zakat Funds Through Maqasid Shariah: Lessons From Indonesia and Malaysia - Ahyani, Hisam; Mutmainah, Naeli; Adnan, Nurul Ilyana Muhd; Solehudin, Ending; Rahman, Encep Taufik; Huda , Miftakhul (Institut Agama Islam Negeri Metro, 2024)
This study examines the practice of qardhul hasan funded by zakat through the perspective of maqasid sharia, focusing on case studies in Indonesia and Malaysia. Qardhul hasan, defined as an interest-free loan, presents a promising method for effectively utilizing zakat funds; however, its implementation within the framework of Islamic law remains a subject of ongoing debate. A qualitative approach was employed, including content analysis and semi-structured interviews with experts in zakat and Islamic law. The findings indicate that maqasid sharia provides a strong foundation for implementing qardhul hasan, particularly in supporting post-pandemic economic recovery. It is crucial to establish clear parameters and guidelines to ensure that qardhul hasan practices adhere to sharia principles and achieve the goal of social justice. This research advances the current understanding of qardhul hasan by highlighting its potential impact on zakat management and economic recovery. Additionally, it encourages zakat policymakers and practitioners to focus on developing effective systems aligned with maqasid sharia and emphasizes the need for ongoing evaluation and trials to enhance zakat's role in societal welfare.